Green marketing strategies and customer satisfaction in rural accommodations: A configurational approach - Álvaro Dias; Marta Santos; Leandro Pereira (Journal of Tourism, Heritage & Services Marketing)
Purpose: Rural tourism has become more popular in the tourism industry, as it offers unique and personalized experiences. During the COVID pandemic, many rural accommodations (RA) had more bookings. This shows the importance of finding out the factors that make good RA experiences.